Ultrasound-Guided Transversus Abdominis Plane Block Versus Intraperitoneal Instillation of Bupivacaine after Laparoscopic Cholecystectomy – A Randomized Control Trial - Rajesh Matam; Vikas Chawla; Shaleen Trivedi; Ajit Bhardwaj; Shivinder Singh (Journal of Medical Sciences and Health, 2023)
Background: Postoperative pain prolongs hospital stay after laparoscopic cholecystectomy and remains a major challenge during the postoperative period. Effective pain control encourages early ambulation, which significantly reduces postoperative complications. In recent years, multimodal analgesia has been recommended with fewer adverse effects and more effective analgesia. The primary objective of this study was to compare the efficacy of analgesia between Transversus Abdominis Plane Block (TAP) Block and intraperitoneal instillation of bupivacaine by comparing the meantime of the first dose of rescue analgesia in either group and the total supplementary analgesia required. Methods: This retrospective observational study was conducted on 150 patients who underwent laparoscopic cholecystectomy Group 1 comprised of patients who had received Intraperitoneal Bupivacaine for analgesia and Group 2 received TAP Block for pain relief. Results: Time of the first dose of analgesia after surgery was observed earlier in Group 1 as compared to Group 2 (Time – hours: 9.2 ± 2 vs. 12.3 ± 1.6; p = 0.0001. The Total dose of analgesic was higher in the Intra Peritoneal Bupivacaine Group as compared to the TAP group. Conclusion: AP block provided for a better quality of analgesia as assessed by the reduced requirement of intravenous supplementary analgesia which was less in patients who were given TAP Block as compared to local instillation of Bupivacaine. Keywords: Cholecystectomy, Bupivacaine, Transversus abdominis plane block